Catholic Education - Mąkosa, Paweł (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Catholic education faces many challenges, mainly due to secularisation. This applies to both content and methods, as well as teacher training. In response to these challenges, the publication titled "Catholic Education" has been prepared. This topic is understood very broadly and includes all dimensions of education provided within the Catholic Church, in Catholic schools and Catholic communities around the world. The main aim of this reprint is to specify and answer new challenges for Catholic education and Catholic religious education that arise from secularisation and other reasons. This reprint contains 17 chapters authored by researchers from various countries and different traditions. Drawing from their diverse experiences, they not only address the issues within their own environments but also analyse global problems. Papers presenting Catholic education and Catholic religious education in historical, contemporary, and future perspectives are also present.